Street glow customs / Mohamad Zulfadly Bolhassan ... [et al.] - Bolhassan, Mohamad Zulfadly; Ruslan Abdul Ghani, Muhd Hanafi; Abang Abdul Hamid, Abg Mohd Syawal; Josim, Arikasyla; Joseph, Joshua Kebing; Adha, Nadirah (2014)
As we know today, people who lives in the city area will have their own career and responsibilities to perform their daily tasks. Most people will not have time to get rid of the dirt and dusts on their vehicles by themselves because of a busy daily routine. Based on this reason, we can see that there is a big opportunity and potential for us to set up a car wash service which will be able to help with our high quality services that can also save their time. We have decided to establish our business plan and provide car washing services at Matang Jaya, Kuching. Observation has been conducted and we found out that this area have a big market and a very high demand.